Assessing the Effects of a Minor CIR‐HSS Geomagnetic Storm on the Brazilian Low‐Latitude Ionosphere: Ground and Space‐Based Observations - F. S. Chingarandi; C. M. N. Candido; F. Becker‐Guedes; O. F. Jonah; S. P. Moraes‐Santos; V. Klausner; O. O. Taiwo (Space Weather)
Abstract This paper investigates the effects of a minor G1 Co‐rotating Interaction Region (CIR)/High‐Speed Stream (HSS)‐driven geomagnetic storm that occurred on (13–14 October 2018), during deep solar minimum. We used simultaneous observations from multiple instruments, namely; ground‐based Global Navigation Satellite Systems (GNSS) receivers, a Digisonde, ground magnetometers, and space‐based observations from the National Aeronautics and Space Administration Global‐scale Observations of Limb and Disk (GOLD) and SWARM missions. This study presents a detailed picture of the low‐latitude ionosphere response over the Brazilian sector during a minor storm. Our results showed that the minor CIR/HSS‐driven storm caused a positive ionospheric storm of over ∼20 TECU in magnitude. For the first time, periodic post‐sunset irregularities and Equatorial Plasma Bubbles, equatorial plasma bubbles, were analyzed using GOLD FUV OI 135.6 nm emission, Total Electron Content (TEC) maps, Rate of TEC index, ROTI, and TEC gradients. Fluctuations in the interplanetary magnetic field Bz and changes in the thermospheric column density ratio (∑O/N2) are discussed as the main sources of ionospheric changes during the storm. This paper highlights the importance of monitoring and understanding the impact of Sun‐Earth interactions and provides insight into the behavior of the low‐latitude ionosphere during minor geomagnetic storms.